Case study on the effect of epidural analgesia on pain management during labour. - Ho, SE; Sumathi U; Ismail MS; Choy, YC; Ahmad Zailani Hatta; Liu, CY (Penerbit UKM, 2013)
Child birth is associated with severely painful experience for the parturient, and often exceeds one’s expectations. Even though, severe pain is non life-threatening condition in healthy parturient women, it may lead to undesired neuropsychological consequences. When no analgesia was used, postnatal depression may be more common, and this labour pain leads to the development of post-traumatic stress disorder. Epidural analgesia is now considered gold standard for effective pain relief during labour. We here report a case of a 37-year-old G1 P0 patient at term gestation who successfully used epidural analgesia for labour pain management.